Off road racing - McKenna, A. T. (Edina, Minn. : Abdo & Daughters, 1998)
Describes the nature, vehicles, and competitions of off-road racing, focusing on four-wheel drive race vehicles such as Range Rovers, Landcruisers, and Jeeps.
Includes index.
Keywords: Off-road racing -- Juvenile literature; Off-road racing; Off-road vehicles